Finite Element Analysis of Elliptical Hollow and Concrete Filled Tube Columns - Jamaluddin, Norwati; Lam, D.; Ye, D. (International Journal of Integrated Engineering, 2009)
Concrete filled tube (CFT) columns have been used as primary axial load-carrying members in high-rise building especially in seismic zones. The structural member has become popular as it has a number of distinct advantages over an equivalent steel, reinforced concrete, or steel-reinforce concrete structural member. This paper is intended to presents numerical modeling of elliptical concrete-filled steel tube columns. Elliptical steel tube is relatively a new shape used as composite columns structure and currently the data for the column is insufficient with very limited understanding therefore it deserve further investigation. This project will investigate the behaviour, capacity and failure pattern up to and beyond the ultimate load of this cross-sectional shape of composite column. Finite element program, ABAQUS also has been used as this method allows the analyses of complex structures and structural phenomena. In order to study the nonlinear response, three dimensional finite element model is develop by considering material non-linearity of the structure.